Anti-Oxidant Phytochemicals as Potential Treatments for Age-Related Macular Degeneration - A. Shahandeh; S. Purushothuman; K. Martin; M. Graham; D.M. Johnstone; E.A. Milward (Journal of Antioxidant Activity, 2015)
Age-related macular degeneration (AMD) is responsible for a substantial proportion of severe visual impairment and blindness in people over 50 years of age. Current treatments for AMD are not effective in all patients and a proportion of patients who respond well to the treatment will still eventually develop central visual impairment. Despite all efforts to develop safe and efficient medications for AMD, as yet pharmacological approaches have failed to provide fully effective treatments for this condition. Various lines of evidence attest to the contributions of oxidative stress in the etiology of AMD. Anti-oxidant nutrients may be valuable preventive or therapeutic agents however complementary therapies can become widely adopted without sufficient knowledge of the real advantages and liabilities. This review considers the interventional potential of some common phytochemicals for treating AMD, primarily focusing on clinical and epidemiological evidence of potential public health relevance.
Keywords: Age-Related Macular Degeneration